Undergraduate Training in ENT Head and Neck Surgery in Nepal: Is there any uniformity? - Guragain, R; Bhatta, R (Nepalese Journal of ENT Head and Neck Surgery, 2011)
DOI: 10.3126/njenthns.v1i1.4736 Nepalese J ENT Head Neck Surg Vol.1 No.1 (2010) p.27-29